LO20: Student Run Simulation Team: A near-peer approach to simulation education. (15th May 2017) - Bouwsema, M.; Turner, S.; Saleh, D.; Rogers, P.; Franke, J.; Nicholas, J.A.; Polsky, Z.; Pfaff, M.; Charania, I.; Clark, M.
Abstract : Introduction/Innovation Concept: Student Run Simulation Team (SRST) is an extracurricular medical student group that provided peers with opportunities to learn and teach principles of acute care medicine in a simulated environment. Early exposure to simulation has been identified as a way for medical students to engage in self-directed education. SRST operated through a peer-led model. Senior medical students designed and delivered didactic sessions, simulation scenarios, and debriefed the scenarios to emphasise targeted objectives.Methods: Informal interviews conducted by the SRST as part of a needs analysis identified barriers to an effective transition from pre-clerkship to clerkship. Specifically, principles of team dynamics including effective communication and role clarification in emergency situations were identified as areas where students lacked confidence. The curriculum focused on leadership and an effective team approach to common acute presentations. SRST members acquired simulation skills under the guidance of a simulation team at the University of Calgary. In the inaugural year, 8 second year students developed and delivered the curriculum to 16 first year students. Quality improvement surveys and participant feedback contributed to ongoing program review and refinement.Curriculum, Tool, or Material: Didactic lectures and task-trainer based skills sessions were created to assist the medical students in developing a foundational approach to a patient presenting to the emergency department. Three distinct simulations of increasing complexity were designed for students to build on their skills. SRST members worked with simulation consultants during 4 custom designed training sessions to develop simulation skills (design and debriefing). The distinguishing aspect of SRST is an emphasis on the non-technical skills of teamwork, leadership, and communication, rather than knowledge acquisition alone. The structure also included a succession plan for continued peer-led education where the student participants will form the next year's team and will receive similar simulation education.Conclusion: SRST is the first student-run simulation initiative to be established in a Canadian medical school. This near-peer team allowed for early practice of non-technical skills in emergency settings. SRST facilitated opportunities for simulation education for both the junior students as participants, and the senior medical students as educators. This is an ongoing initiative, with plans to continue program development in future years.